2014
DOI: 10.1038/aps.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Selective α1B- and α1D-adrenoceptor antagonists suppress noradrenaline-induced activation, proliferation and ECM secretion of rat hepatic stellate cells in vitro

Abstract: Aim: To explore the effects of noradrenaline (NA) on hepatic stellate cells (HSCs) in vitro and to determine the adrenoceptor (AR) subtypes and underlying mechanisms. Methods: The distribution and expressions of α 1A -, α 1B -, and α 1D -ARs in HSC-T6 cells were analyzed using immunocytochemistry and RT-PCR. Cell proliferation was evaluated with MTT assay. The expression of HSC activation factors [transforming factor-β 1 (TGF-β 1 ) and α-smooth muscle actin (α-SMA)], extracellular matrix (ECM) secretion factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…NE and ACh released from these terminals may bind to receptors on the stem cells and/or the TA cells to affect proliferation. Both NE and ACh have been shown to directly alter proliferation in other cell types, mediated through a variety of adrenoreceptor and muscarinic receptor subtypes (Cruise et al 1985;Geloen et al 1988;Bronnikov et al 1992;Oben et al 2003a,b;Liu et al 2014Liu et al , 2017Sloniecka et al 2015;Morgan et al 2016). However, in contrast to other organ systems, the gastrointestinal (GI) tract is innervated by the enteric nervous system (ENS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NE and ACh released from these terminals may bind to receptors on the stem cells and/or the TA cells to affect proliferation. Both NE and ACh have been shown to directly alter proliferation in other cell types, mediated through a variety of adrenoreceptor and muscarinic receptor subtypes (Cruise et al 1985;Geloen et al 1988;Bronnikov et al 1992;Oben et al 2003a,b;Liu et al 2014Liu et al , 2017Sloniecka et al 2015;Morgan et al 2016). However, in contrast to other organ systems, the gastrointestinal (GI) tract is innervated by the enteric nervous system (ENS).…”
Section: Discussionmentioning
confidence: 99%
“…,b; Liu et al. , ). Twenty‐four hours after treatment administration, Matrigel was dissolved using 1 mL QIAzol (QIAGEN; Germantown, MD), the cells vortexed, and stored at −80°C to await processing (see Quantitative real time polymerase chain reaction).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron-microscopic studies have shown that HSCs, the major fibrogenic cells in the liver, are in contact with nerve fibers in the human liver [22]. In addition, several neuronal genes, including adrenergic receptors, are expressed in HSCs [48], and catecholamines are known to aggravate stress-induced liver diseases (e.g., cirrhosis) [49]. In this study, sFRP1 was chosen as the central molecule for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In addition, chloroethylclonidine as an irreversible a 1B adrenoceptor antagonist and pyrrolidin-2-one derivatives as selective a 1B adrenoceptor antagonists have been reported. 11,12 In the present study, however, we aimed to use other structural motifs for designing potent and selective a 1B adrenoceptor antagonists. In this Letter, we report the synthesis and structure-activity relationship of indole derivatives that show high affinity and selectivity for the a 1B adrenoceptor.…”
mentioning
confidence: 99%